Perbedaan Tingkat Pengetahuan Pasien Sectio Caesarea Sebelum dan Sesudah Edukasi Mobilisasi Dini Berbasis Video di RSUM Siti Aminah Bumiayu - Dwi Cahyaningsih; Amin Susanto; Atun Raudotul Marifah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Early mobilization in post-Caesarean section patients is an important effort to accelerate the recovery process and prevent complications; however, many patients still lack understanding of its importance and are reluctant to perform it. Video-based health education is considered an effective method to improve patient knowledge as it presents information in a visual and engaging manner. This study aimed to determine the difference in the level of knowledge regarding early mobilization among Caesarean section patients before and after receiving video-based education. This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 25 respondents selected using purposive sampling technique. The instrument used was a knowledge questionnaire, and data were analyzed using the Paired Samples t-Test. The results showed an increase in the average knowledge level of respondents after the intervention. The mean knowledge score before the intervention (pretest) was 47.73 and increased to 76.26 after the intervention (posttest). Statistical analysis showed a p-value of 0.001 (p < 0.05), indicating a significant difference in knowledge levels before and after the video-based education. Therefore, it can be concluded that video-based education is effective in improving knowledge about early mobilization in post-Caesarean section patients.